Student Perceptions Regarding the Mind Map Application in Mathematical Education - Violeta Cvetkoska (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
The aim of this paper is to observe the respondents' (second-year students') perceptions regarding the mind map tool application in the classes of the course Mathematical Methods, and with its application to learn the course material. A survey was conducted for this research. Based on the respondents' answers, 11 uses of the mind map tool application in teaching and 12 uses in learning the material have been determined. Besides its uses, 3 limitations of this tool have also been found. Introducing mind map in teaching the course Mathematical Methods was suitable for almost all respondents (with the exception of one respondent). Homework – making a summarized mind map for a particular chapter, was helpful for learning the material of that chapter for almost all respondents, except for one. Besides this, it has also been determined that the majority of the respondents would like to use this tool in other courses as well.
Keywords: C6; C83; I23; 330; teaching; learning; students; mind mapping; mind map